In Vitro Evaluation of the Growth Potential of Chlorella Sp. and Desmodesmus Sp for Use as a Biological Phycoremediation Agent in Wastewater - Vergara, Donicer E. Montes; Mendoza, Yelitza Aguas; Cordero, Alexander Pérez (Journal of Ecohumanism, 2024)
The objective of the present study was to evaluate in vitro the growth behaviour of Chlorella sp. and Desmodesmus sp. in a phyco-reactor in a nutritional source with fertilizer and wastewater, artificial light and sunlight to determine the growth conditions for their use as a biological agent to remediate organic load in wastewater in the department of Sucre, Colombia. Chlorella sp. and Desmodesmus sp. were subjected to two nutrient sources (Nutriofoliar 4 Nm fertilizer and wastewater) and light source (artificial light and sunlight) in a phyco-reactor for 20 hours under agitation at 4000 rpm. The results show differences in the growth behaviour of both microalgae according to the nutritional source and the type of light. In the presence of Nutrifoliar the microalgae have a difference in the growth behaviour being higher for Chlorella sp with an exponential phase up to 19 days and a duration of 17 days with respect to Desmodesmus sp, which was 12 days. With respect to the nutritional source wastewater, the same growth behaviour was observed, with the presence of less growth compared to when they were grown in Nutriofoliar, likewise, in both microalgae the exponential phase was observed to be shorter in days when they were grown in wastewater. There is a need to study the growth behaviour of those microalgae species as an alternative to remediate wastewater in the field.